Variability in the Heritability of Body Mass Index: A Systematic Review and Meta-Regression - Elks, Cathy E.; Den Hoed, Marcel; Zhao, Jing Hua; Sharp, Stephen J.; Wareham, Nicholas J.; Loos, Ruth J.; Ong, Ken K. (Frontiers in Endocrinology, 2012)
Evidence for a major role of genetic factors in the determination of body mass index (BMI) comes from studies of related individuals. However, heritability estimates for BMI vary widely between studies and the reasons for this remain unclear. While some variation is natural due to differences between populations and settings, study design factors may also explain some of the heterogeneity. We performed a systematic review that identified eighty-eight independent estimates of BMI heritability from twin studies (total 140,525 twins) and twenty-seven estimates from family studies (42,968 family members). BMI heritability estimates from twin studies ranged from 0.47 to 0.90 (5th/50th/95th centiles: 0.58/0.75/0.87) and were generally higher than those from family studies (range: 0.24-0.81; 5th/50th/95th centiles: 0.25/0.46/0.68). Meta-regression of the results from twin studies showed that BMI heritability estimates were 0.07 (P=0.001) higher in children than in adults; estimates increased with mean age among childhood studies (+0.012 per year, P=0.002), but decreased with mean age in adult studies (-0.002 per year, P=0.002). Heritability estimates derived from AE twin models (which assume no contribution of shared environment) were 0.12 higher than those from ACE models (P<0.001), whilst lower estimates were associated with self-reported versus DNA-based determination of zygosity (-0.04, P=0.02), and with self-reported versus measured BMI (-0.05, P=0.03). Together, the above factors explained 47% of the heterogeneity in estimates of BMI heritability from twin studies. In summary, while some variation in BMI heritability is expected due to population-level differences, study design factors explained nearly half the heterogeneity reported in twin studies. The genetic contribution to BMI appears to vary with age and may have a greater influence during childhood than adult life.